Anthracnose: an economic disease of cassava in Africa - Fokunang, C.N.; Dixon, Alfred G.O.; Ikotun, T.; Tembe-Fokunang, E.A.; Akem, C.N.; Asiedu, Robert (Science Alert, 2001)
Cassava anthracnose disease (CAD) caused by the fungus Colletotrichum gloeosporioides f.sp. manihotis has become one of the major economic diseases of cassava in Africa. The expansion of cassava production farmlands particularly in the humid rainfall zones of West and Central Africa has led to an increase in pathological problems of the crop. The increased epidemic levels of CAD had caused significant crop failure leading to severe food shortages for the poor subsistent farming population depending on the crop for their livelihood. This paper reviews the importance of the crop in terms of food security, CAD disease symptoms, epidemiology, yield losses and the possible control options within the frame work of integrated pest management systems (IPMS).